2006
DOI: 10.1108/00483480610636786
|View full text |Cite
|
Sign up to set email alerts
|

Effects of training framing, general self‐efficacy and training motivation on trainees' training effectiveness

Abstract: PurposeThe purpose of this paper is to examine the effects of training framing from supervisors on trainee self‐efficacy and training motivation, and further test how these variables subsequently influence overall training effectiveness.Design/methodology/approachThe design of the study includes longitudinal, self‐report and objective measures. Data were collected from 126 employees who entered a training program aiming at introduction of computer software operation and design. Participants were asked to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
164
0
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(181 citation statements)
references
References 37 publications
9
164
0
8
Order By: Relevance
“…Tai (2006) in his study, the role played by immediate supervisor is crucial to develop employee's self-efficacy hence improve training motivation that supported with Kirkpatrick theory. Study found, it give an impact towards trainees reaction, learning and transfer motivation.…”
Section: Relationship Between Self-efficacy and Training Motivationmentioning
confidence: 74%
See 2 more Smart Citations
“…Tai (2006) in his study, the role played by immediate supervisor is crucial to develop employee's self-efficacy hence improve training motivation that supported with Kirkpatrick theory. Study found, it give an impact towards trainees reaction, learning and transfer motivation.…”
Section: Relationship Between Self-efficacy and Training Motivationmentioning
confidence: 74%
“…Employees with higher self-efficacy tend to be more productive and motivated to participate in the training program and willing to learn new knowledge (Tai, 2006). Empirical studies have shown a positive relationship between self-efficacy and training motivation (Colquitt, 2000).…”
Section: Relationship Between Self-efficacy and Training Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Five items assess health, four items assess education, and seven items assess micro-credit, respectively.  The four dimensions of training evaluation is represented by 28 items derived from Barker (1997), Barcala, Martin, and Gutierrez (2000), Wilson (2000), Pau (2001), Price (2001), Tai (2006), and Al-Eisa, Furayyan, and Alhemoud (2009), consisting of three adopted, 20 adapted, and five constructed to measure NGOs' training programmes. 11 items assess training-reaction, seven items assess training-learning, five items assess training-behaviour, and five items assess training-result.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies in this category are Bong and Choi (2000); Thompson, Meriac and Cope (2002);Meyer et-al (2002);Brown, et-al. (2003); Tai (2006); Crippen and Earl (2007); Yukselturk and Bulut (2007). Other studies examined gender, access to and use of the online environment.…”
Section: Literature Reviewmentioning
confidence: 99%